A Model for Utilizing Common Land for Investment Through HPL that Strengthens the Position of Indigenous Communities - Lenny Husna; Muskibah Muskibah; Dwi Suryhartati (Journal of Adat Recht, 2026)
This research stems from significant changes in national agrarian policy through Government Regulation 18/2021 and Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) 14/2024, which for the first time opened the possibility of establishing customary land as a source of Land Management Rights (HPL) and recognizing indigenous communities as their holders. However, this recognition remains administrative in nature and is not accompanied by a substantive framework that ensures the protection of rights, full participation, and fairness for indigenous communities in investment practices. The research method used is normative legal research with legislative, conceptual, and comparative approaches, enriched by empirical findings from HPL management practices in various indigenous territories. This approach allows for an in-depth analysis of regulatory disharmony, administrative practices, and socio-legal dynamics that influence the position of indigenous communities in the HPL scheme. The results show that although the national legal system has formally recognized customary land, significant normative and institutional gaps remain. The implementation of HPL in the field often weakens the bargaining position of indigenous communities due to limited legal access, the absence of substantive participation mechanisms, and the dominance of state and investor interests in the decision-making process. In addition, regulations regarding timeframes, cooperation mechanisms, and ecological protection still do not provide adequate legal certainty.